135 Natural History of Midline Brain Shift Following Hemispherectomy and its Association with Cerebral Spinal Fluid Diversion in Pediatric Epilepsy. (1st April 2022) - Phillips, H. Westley; Maniquis, Cassia A. B.; Duby, Shannon L.; Chen, Jia-Shu; Bergeron, David; Nagahama, Yasunori; Ibrahim, George; Weil, Alexander G.; Fallah, Aria
Abstract : INTRODUCTION: Hemispherectomy and its modern variants are effective surgical treatments for medically intractable unihemispheric epilepsy. While complications of hemispherectomy such as postoperative hydrocephalus are well documented, a less-studied phenomenon of postoperative midline brain shift (MLBS) has only been described anecdotally and never formally studied. METHODS: A retrospective review of consecutive pediatric patients who underwent hemispherectomy for medically refractory epilepsy at UCLA between 1994 and 2018 was performed. Patients were stratified by severity of MLBS, shunt placement, type of shunt valve, and opening pressure. MLBS progression was evaluated within groups using repeated measures ANOVA and compared between groups using ANCOVA while adjusting for follow-up time and baseline postoperative MLBS. RESULTS: In total, 97 patients with a median follow-up of 17.7 months were analyzed in this study. Of these patients, 27 (28%) required CSF diversion via shunt placement in the ipsilateral cavity for post-hemispherectomy hydrocephalus. In non-shunted patients, average MLBS immediately following hemispherectomy and at last follow-up was 4.8 ± 4.7 and 8.3±6.4 mm, respectively. In shunted patients, average MLBS immediately after hemispherectomy and at latest follow-up following shunt placement was 6.5 ± 3.3 and 14.6 ± 9.5 mm, respectively. MLBS increased for both shunted and non-shunted patients between first and last follow-up. However, MLBS progression between first and last follow-up was significantly greater in the shunted cohort than the non-shunted cohort [F (1, 92) = 5.33, p = 0.023]. Placement of valves with higher opening pressure settings did not significantly increase MLBS relative to non-shunted patients [F (1, 73) = 0.1, p = 0.765], whereas MLBS was significantly greater with low opening pressure settings [F (1, 85) = 8.5, p = 0.004]. Furthermore, severe MLBS was significantly associated with debilitating headaches (p = 0.042). CONCLUSION: Patients undergoing hemispherectomy often develop postoperative MLBS. The progression of MLBS is significantly exacerbated by CSF shunting of the ipsilateral post-surgical cavity, specifically when accomplished with lower opening pressure settings. Severe MLBS is associated with severe headaches, suggesting that MLBS exacerbation may be related to overshunting.